2010
DOI: 10.1177/0734242x10375333
|View full text |Cite
|
Sign up to set email alerts
|

Seismic stability analysis of expanded MSW landfills using pseudo-static limit equilibrium method

Abstract: Capacity expansion of existing landfills is the most economical alternative to constructing new landfills where cost of land is prohibitive. From the safety point of view, the stability analyses of existing landfills expanded either vertically and/or laterally are required for different stages of construction, operation and during closure of a landfill. In the present study, a pseudo-static limit equilibrium seismic stability analysis was performed for a typical side-hill type municipal solid waste (MSW) landf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…e results showed that landfill expansion is more likely to occur from seismic loads, and the extended landfill was more likely to slide along the interface between the new landfill and the old landfill under seismic loads. Choudhury and Savoikar [11] used a pseudostatic limit equilibrium method to consider the impact of horizontal and vertical seismic acceleration and analyzed the seismic stability of the vertical expansion landfill. e results showed that the average factor of safety decreased as both horizontal and vertical seismic accelerations increased.…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that landfill expansion is more likely to occur from seismic loads, and the extended landfill was more likely to slide along the interface between the new landfill and the old landfill under seismic loads. Choudhury and Savoikar [11] used a pseudostatic limit equilibrium method to consider the impact of horizontal and vertical seismic acceleration and analyzed the seismic stability of the vertical expansion landfill. e results showed that the average factor of safety decreased as both horizontal and vertical seismic accelerations increased.…”
Section: Introductionmentioning
confidence: 99%
“…The seepage force reduces the effective stress between the soil particles, which consequently results in failure of the landfill cover system. The impacts of the seepage force on the stability of landfill cover systems have been widely investigated through analytical methods for landfill cover systems with uniform profile (Choudhury and Savoikar, 2011; Feng and Gao, 2012; Giroud et al, 1995; Soong and Koerner, 1995; Yamawaki et al, 2017). The obtained results revealed that the seepage force has a significant negative effect on the stability of the landfill cover system.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods to assess the performance of the landfill cover systems during an earthquake (Matasovic and Kavazanjian, 2006). The most commonly used seismic analytical method for evaluation the stability of landfill cover systems under seismic loading condition is pseudo static analysis (Kavazanjian, 1998; Choudhury and Savoikar, 2011). In this method, seismic shaking is modeled as a force which acts on the free body diagram in a limit equilibrium analysis in the case of static condition (Nadi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the expanded landfill with a trapezoidal berm, Qian and Koerner (2009) analyzed the static stability of the landfill based on both over-berm and under-berm failure conditions. Then Choudhury and Savoikar (2011a) investigated the pseudo-static seismic stability of the landfill based on both over-berm and under-berm failure conditions. Although Choudhury and Savoikar (2011a)'s method is based entirely on Qian and Koerner (2009)'s static model of the expanded landfill and their related assumptions, the average safety factor of the two methods is different even when the parameters of the two methods are the same.…”
Section: Introductionmentioning
confidence: 99%